THE EFFECT OF PERFORMANCE APPRAISAL, COMPENSATION, AND JOB SATISFACTION TO EMPLOYEE ENGAGEMENT AT STIKES DR. SOEBANDI JEMBER - Quinta Hanum, Ariefa; Indah Handayani, Yuniorita; Supardi, Supardi (MBA : Journal of Management and Business Aplication, 2022)
The purpose of this study was to analyze the effect of Performance Appraisal, Compensation, and Job Satisfaction either partially or simultaneously on Employee Engagement on STIKES dr. Soebandi. This type of research is quantitative research, with the type of data used is primary data. The sampling technique used the census technique, with a total sample of 86 respondents. The data analysis method used multiple linear regression analysis. The results of the analysis show that partial job appraisal has no significant effect on employee engagement because it produces a significance level above 0.05. Then, the partial compensation has a significant effect on employee engagement because it produces a significance level below 0.05. Then, the partial job satisfaction has a significant effect on employee engagement because it produces a significance level below 0.05.